2013
DOI: 10.1253/circj.cj-12-0925
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Oscillatory Breathing and Cardiopulmonary Function During Exercise in Cardiac Patients

Abstract: Cardiopulmonary exercise testing (CPX) is a useful clinical tool for evaluating the severity of disease and the limitations of activities of daily life in cardiac patients. 9 As described by the Fick's equation, O2 uptake (V O2) is the product of cardiac output and the arteriovenous O2 difference. Among the parameters obtained from CPX, the peak V O2 is traditionally considered as the gold standard for identifying patients with a poor prognosis and selecting candidates for cardiac transplantation. 10 The slope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
1
14
0
4
Order By: Relevance
“…Many epidemiologic studies have demonstrated that poor lung function, as indicated by a low forced expiratory volume in 1 s (FEV1) and forced vital capacity (FVC), is associated with an increased risk of coronary artery disease (CAD), stroke, and cardiovascular death. [1][2][3][4][5][6][7] This risk is independent of cigarette smoking, 3,8,9 which is a shared risk factor for lung function and cardiovascular disease (CVD). 8, 9 Moreover, lung function parameters are a powerful predictor of cardiovascular mortality compared with socioeconomic position, cardiovascular risk factors (ie, serum cholesterol and blood pressure), 7,10 and Framingham risk score alone.…”
Section: Subjectsmentioning
confidence: 99%
“…Many epidemiologic studies have demonstrated that poor lung function, as indicated by a low forced expiratory volume in 1 s (FEV1) and forced vital capacity (FVC), is associated with an increased risk of coronary artery disease (CAD), stroke, and cardiovascular death. [1][2][3][4][5][6][7] This risk is independent of cigarette smoking, 3,8,9 which is a shared risk factor for lung function and cardiovascular disease (CVD). 8, 9 Moreover, lung function parameters are a powerful predictor of cardiovascular mortality compared with socioeconomic position, cardiovascular risk factors (ie, serum cholesterol and blood pressure), 7,10 and Framingham risk score alone.…”
Section: Subjectsmentioning
confidence: 99%
“…According to Dhakal et al, ventilatory instability and oscillations may arise from (1) increased circulatory delay, (2) increased chemosensitivity, (3) pulmonary congestion or (4) ergoreflex signaling. 12 In this issue of the Journal, Kato et al found that cardiac patients with more impaired cardiopulmonary dysfunction during exercise, as reflected in the CPX indices, have a longer CL of oscillating V E. 10 This finding supports the hypothesis by Murphy et al that oscillatory breathing is an important surrogate for hemodynamic impairment in patients with heart failure. 13 Heart failure patients with exercise oscillatory ventilation (HF + EOV) demonstrated a greater degree of hemodynamic impairment at rest, as evidenced by higher resting right atrial pressure, pulmonary arterial pressure, and pulmonary capillary wedge pressure and lower cardiac index (CI) compared with heart failure patients without exercise oscillatory ventilation (HF -EOV).…”
mentioning
confidence: 62%
“…This would also support the hypothesis that the circulation delay is an important factor determining oscillatory breathing, because the circulation time becomes shorter with the increased intensity of exercise as the result of the increase in cardiac output. 10 Exercise oscillatory breathing is a noninvasive, easily recognizable and reproducible submaximal exercise parameter observed during CPX. The prognostic significance of exercise oscillatory breathing and the apparent modifiability of oscillatory breathing with heart failure interventions make oscillaeriodic breathing, which is a form of irregular breathing characterized by cyclic variation of ventilation at rest and exercise, has been a recognized feature of heart failure for almost 2 centuries.…”
mentioning
confidence: 99%
“…The O2 uptake (VO2), CO2 output (VCO2), and VE were measured throughout the test using an Aeromonitor AE-300s (Minato Medical Science, Osaka, Japan), as previously described. 11,12) Before the parameters from the respiratory gas analysis were calculated, breathby-breath data were interpolated to give second-by-second values. These second-by-second values were then calculated as successive 3-second averages and translated into a 5-point moving average.…”
Section: Figurementioning
confidence: 99%